Assessment for fungal, mycotoxin and insect spoilage in maize stored for human consumption in Zambia - Kankolongo, M.A.; Hell, K.; Nawa, I.N. (Wiley, 2009)
BACKGROUND: Maize constitutes the main staple food and most important crop grown in Zambia. However, maize incursconsiderable losses both in field and storage due to pathogens and insects. Some of the pathogens and resultant mycotoxinsreduce the nutritional quality of the product. Mycotoxins are toxigenic fungal compounds that can cause cancer and suppressgrowth. In spite of this health hazard, there has been very little research to document their occurrence. Maize grains stored forhuman consumption were sampled from different agro-ecosystems (forest, valley and plateau areas) of three agroecologicalzones (high, mid and low altitude).RESULTS: Several fungal genera were recovered among whichAspergillus flavus, A. niger, Fusarium verticillioides, F. solani,Rhizopus stoloniferandPenicilliumspp. were prevalent. The weevilSitophilus zeamaisand the larger grain borerProstephanustruncatuswere the most damaging. Enzyme-linked immunosorbent assay (ELISA) tests yielded fumonisins and aflatoxinsranging between 0.02 and 21.44 ppm, and 0.7 and 108.39 ppb in 96.4% and 21.4% of samples, respectively. Fumonisin wasmore pronounced in villages in forest areas whereas aflatoxin was highest in valley and forest areas in Zone II.CONCLUSION: Strategic interventions to curtail fungal, mycotoxin and insect contamination should be directed towardsimproved agronomic and post-harvest practices of maize from fields to consumers.